Cost-effectiveness of hypothermic machine preservation versus static cold storage in renal transplantation. - Groen, H; Moers, C; Smits, J; Treckmann, J; Monbaliu, D; Rahmel, A; Paul, A; Pirenne, J; Ploeg, R; Buskens, E (2012)
Static cold storage (CS) is the most widely used organ preservation method for deceased donor kidney grafts but there is increasing evidence that hypothermic machine perfusion (MP) may result in better outcome after transplantation. We performed an economic evaluation of MP versus CS alongside a multicenter RCT investigating short- and long-term cost-effectiveness. Three hundred thirty-six consecutive kidney pairs were included, one of which was assigned to MP and one to CS. The economic evaluation combined the short-term results based on the empirical data from the study with a Markov model with a 10-year time horizon. Direct medical costs of hospital stay, dialysis treatment, and complications were included. Data regarding long-term survival, quality of life, and long-term costs were derived from literature. The short-term evaluation showed that MP reduced the risk of delayed graft function and graft failure at lower costs than CS. The Markov model revealed cost savings of $86,750 per life-year gained in favor of MP. The corresponding incremental cost-utility ratio was minus $496,223 per quality-adjusted life-year (QALY) gained. We conclude that life-years and QALYs can be gained while reducing costs at the same time, when kidneys are preserved by MP instead of CS.